Development of a Simple Single-Axis Motion Table System for Testing Tilt Sensors. (2017) - Yuliza, Elfi; Habil, Husni; Salam, Rahmat Awaludin; Munir, Muhammad Miftahul; Abdullah, Mikrajuddin; Khairurrijal,
Abstract: Advanced applications of a tilt sensor, such as in disaster management, requires a system to test the performance of a tilt sensor before being applied in the field. Commercially, Ideal Aerosmith developed various models of two- and three-axis positioning and rate table system with high resolution and accuracy. However, the utilization of the system is more suitable for military and aerospace technologies that require very high resolution and accuracy. The system is therefore expensive and not portable. This paper reports the development of simple single-axis motion table system to provide precise position and motion rate for testing a tilt sensor. The system was developed by using a stepper motor in which the direction of the movement can be set by adjusting the encountered electrical current in the motor. The resolution of stepper motor used in the developed system was 0.9 o /step, whereas various types of tilt sensors and their applications require a tester system with higher resolution. A gears system was employed to improve the stepper motor resolution used in the developed motion table system. Under a certain design of the gears system, the developed motion table system could achieve a higher resolution of 0.018 o /step. It has been found that the relationship between the number of steps of the stepper motor and the rotation angle of the developed motion table system was linear and same for forward and backward steps. Moreover, the developed single-axis motion table system moved consistently for either forward (up) or backward (down) rotations in the range of 0 to 180 o as assessed by the accelerometer-based tilt sensor. The developed single-axis motion table system can therefore be used for testing tilt sensor.